Spurious correlation in estimation of the health production function: A note - Sule Akkoyunlu; Frank R. Lichtenberg; Boriss Siliverstovs; Peter Zweifel (University of Zurich, Socioeconomic Institute, 2009)
In this paper, we address the issue of spurious correlation in the production of health in a systematic way. Spurious correlation entails the risk of linking health status to medical (and nonmedical) inputs when no links exist. This note first presents the bounds testing procedure as a method to detect and avoid spurious correlation. It then applies it to a recent contribution by Lichtenberg (2004), which relates longevity in the United States to pharmaceutical innovation and public health care expenditure. The results of the bounds testing procedure show longevity to be linearly related to these two factors. Therefore, the estimates reported by Lichtenberg (2004) cannot be said to be result of spurious correlation, to the contrary, they very likely reflect an effective relationship, at least for the United States.
Keywords: H51; I12; J18; C22; C32; O33; 330; Health; Life expectancy; Innovation; Pharmaceuticals; Health care expenditure; Cointegration; Gesundheitsversorgung; Sterblichkeit; Innovation; Pharmazeutisches Produkt; Gesundheitskosten; Kointegration; Schätzung; USA